A study & implementation of kaizen strategy for line production (cap cam shaft) in Sapura Machining - Wan Nurul Athia, Wan Mohd Zamani (2016)
This thesis deal with Kaizen strategy which is implementation of 5S and purpose for standardized work. The project background is in Sapura Machining Corporation. The objective of this thesis is to implement the 5s method in line production Capcam Shaft and to purpose a standardized work for a better work sequence. The project method conducted is by doing the Gemba Walk and observed the OFI (Opportunity for Improvement). 5S had been implement based on the problem observe from the line production. The aim is to increase the cleanliness, safety for operator by using PPE (Personal Protective Equipment) and the training to discipline the operator. For standardized work, cycle time need to be record for before and after. The non-value added is reduce in the time taken to increase the line efficiency. Standardized work is made using simulation of Tecnomatix Software which is the plant need to be arrange like actual layout and insert the cycle time for each machine. For the result, 5S method that had been implement has been awarded as a ‘Best Line 3S Finding Activity’ and ‘5S best Practice’. For standardized work the line efficiency increase from 70.23% to 95.43% and the transportation material time success to be reduce from 49.71% to 4.57%.